1921
DOI: 10.1002/cber.19210540828
|View full text |Cite
|
Sign up to set email alerts
|

Über Untersuchungen in der Tetraarylbutan‐Reihe und über das 1.1 4.4‐Tetraphenyl‐butatrien. (4. Mitteilung über die Reduktion organischer Halogen‐verbindungen.)

Abstract: 1) M. M. Richter, Lexikon der KohlenstoFfverbindungen. bsnzol bei 800 und nsah Entfemung des Benzols enteprechend den Angaben von Valeur') bei 1210 eobrmolren. (&Baa+CfHs. Ber. C 92.7, H 7.3, CsH6 17.93. Gef. 92.5, s 7.6, s 18.3. Eine vom Benzol befreite Probe lieferte aue Alkohol tafefE6mige Krystalle, ebenfalls vom Schmp. 1210. C~BH~G. Ber. C 92.8, H 7.2.Gef. B 92.5, B 7.6. Auch beim Schiitteln von 0.5 g Tetraphenyl-butatrien mit Alkohsl und Palladium-Tierkohle 2, mit Wasserstoff von 1 , Atm. oberdruck unter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
4

Year Published

1922
1922
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 9 publications
0
8
0
4
Order By: Relevance
“…Communications 750 www.angewandte.org lations (PBE1PBE [39][40][41][42] /(def2-)TZVP [43,44] )o nt he cations 2 and 3 showed that al inear C NHC À C C À Ca rrangement is preferred, thus implying that the observed bending is most likely ac rystal-packing effect due to as hallow potential for angle bending (see the Supporting Information). This hypothesis was confirmed by synthesizing an umber of other monocation compounds similar to 2,w hich were characterized by X-ray diffraction (2[PF 6 ], para-F-2[PF 6 ], para-Ph-2[Br];s ee the Supporting Information). An analysis of bond lengths and angles for the C NHC À C C À Ar portion of the cations gave significant variation in the C NHC À C Cb ond angle (from 163.9(3) to 180.08 8), thus showing that this is indeed the one position in each compound where flexibility can be induced during packing for crystallization.…”
Section: Angewandte Chemiementioning
confidence: 81%
See 1 more Smart Citation
“…Communications 750 www.angewandte.org lations (PBE1PBE [39][40][41][42] /(def2-)TZVP [43,44] )o nt he cations 2 and 3 showed that al inear C NHC À C C À Ca rrangement is preferred, thus implying that the observed bending is most likely ac rystal-packing effect due to as hallow potential for angle bending (see the Supporting Information). This hypothesis was confirmed by synthesizing an umber of other monocation compounds similar to 2,w hich were characterized by X-ray diffraction (2[PF 6 ], para-F-2[PF 6 ], para-Ph-2[Br];s ee the Supporting Information). An analysis of bond lengths and angles for the C NHC À C C À Ar portion of the cations gave significant variation in the C NHC À C Cb ond angle (from 163.9(3) to 180.08 8), thus showing that this is indeed the one position in each compound where flexibility can be induced during packing for crystallization.…”
Section: Angewandte Chemiementioning
confidence: 81%
“…[2] Shorter cumulenes, such as [3]cumulenes,w ere first reported by Brand in the early 1920s. [5,6] More recently,Diederich and co-workers have looked at the synthesis and reactivity of these systems [7,8] and an umber of push-pull/donor-acceptor [3]cumulenes. [9,10] Ueta et al have also reported the [2+ +2] cycloaddition of a[3]cumulene with tetracyanoethene.…”
mentioning
confidence: 99%
“…[32,35,36] Strong s donors as end-capping groups of the cumulene chain give their radical speciesaremarkable stability, [26,32,[37][38][39][40] with someo ft hese radicals stable even to air. [39,40] Cumulenes have been known for around100 years, [41] however, [3]cumulenes that have strong s donors as terminal groups, such as N-heterocyclic or cyclic (alkyl)(amino) carbenes (NHCs or CAACs, respectively), have only recently been studied. [1,26,29,30,[37][38][39][40]42] As discussed above, these types of terminal groups significantly change the properties of the carbonc hain with respectt ot he classical [3]cumulenes and allenes.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] In comparison to most other organic molecules,t he structure of [n]cumulenes is unique,namely,the basic frame-work is composed of only sp-hybridized carbon atoms linked by only one type of bond (and terminated with an sp 2hybridized carbon atom). Interest in the synthesis and properties of [n]cumulenes dates back to at least 1921, [7] but until the last few years relatively few studies have explored [n]cumulenes.T he most recent synthetic efforts have provided intriguing details about their chemical and physical properties,such as,for example,their solid-state structure and electronic absorption behavior versus length of the cumulene skeleton. [8] Ad etailed understanding of the redox behavior of conjugated organic molecules is of importance for all charge-transfer processes and should help to facilitate their practical applications as organic semiconductors as well as photovoltaic and multielectron storage materials.N evertheless,t here have been limited studies on the electrochemical behavior of [n]cumulenes.Asingular electrochemical study of [n]cumulenes as af unction of length demonstrates that the first reduction potential is affected dramatically by the molecular length, while the first oxidation potential remains nearly constant.…”
mentioning
confidence: 99%